Unveiling the Determinant factors effecting the willingness to share waqf information among Malaysians - Noraini Yusuff; Fuadah Johari; Nor Syahidah Ishak; Hanim Hj Misbah; Siti Latipah Harun; Nurul Adilah Hasbullah; Siti Hajar Salwa Ahmad Musadik; Azuan Ahmad (Universal Publishers - Boca Raton, Florida, USA, 2024)
Indexed by ERA